Penentuan Fasies, Umur, dan Lingkungan Pengendapan Batuan Karbonat Klastik Formasi Sentolo di Watu Lempeng, Kecamatan Nanggulan, Kabupaten Kulon Progo, Daerah Istimewa Yogyakarta - Nadhip, Muhammad; Alansyah, Apriko Yudhan; Kurniawan, Sandi; Rizqi, Al Hussein Flowers; Erlandi, Muhammad; Haliza, Audia Shafa (ReTII, 2023)
Watu Lempeng is a tourist spot on the Serang River, connecting Banyuroto Village and Sendangsari Village. No research has examined in detail the age conditions and depositional environment in this area, so it is necessary to study geology, especially stratigraphy. The rocks at this location are quite interesting because they look like flat plates that are uniquely arranged along the Serang River. Administratively, the research area is in the Banyuroto Region, Nanggulan District, Kulon Progo Regency. Geographically, it is located at 110Â°9’59.3"E and 7Â°49’24.152"S. The research area is included in the physiography of the Kulon Progo Mountains to the east, precisely in the Sentolo Formation. This study aims to identify age and environment. Research methods include collecting lithology data using measured stratigraphy (MS) methods to determine facies. Selected rock samples were taken for petrographic and paleontological analysis. Petrographic microscopic studies of rocks will interpret the rock facies used as a reference in determining the depositional environment. Paleontological research was carried out to analyze the age and depositional environment. Based on field data, the 46 meter long track was composed of limestone units Grainstone, Packstone and wackestone, showing Foreslope facies. The deposition of these rocks is in the age range N13-N14 (Middle Miocene) and was deposited in the Middle Neritic â€“ Outer Neritic bathymetry (100 â€“ 200 meters). Keywords: Kali Serang, Watulempeng, Sentolo, age, depositional environment